DNA Vaccine-Generated Duck Polyclonal Antibodies as a Postexposure Prophylactic to Prevent Hantavirus Pulmonary Syndrome (HPS) - Brocato, Rebecca; Josleyn, Matthew; Ballantyne, John; Vial, Pablo; Hooper, Jay W. (PLOS ONE, 2012)
Andes virus (ANDV) is the predominant cause of hantavirus pulmonary syndrome (HPS) in South America and the only hantavirus known to be transmitted person-to-person. There are no vaccines, prophylactics, or therapeutics to prevent or treat this highly pathogenic disease (case-fatality 35–40%). Infection of Syrian hamsters with ANDV results in a disease that closely mimics human HPS in incubation time, symptoms of respiratory distress, and disease pathology. Here, we evaluated the feasibility of two postexposure prophylaxis strategies in the ANDV/hamster lethal disease model. First, we evaluated a natural product, human polyclonal antibody, obtained as fresh frozen plasma (FFP) from a HPS survivor. Second, we used DNA vaccine technology to manufacture a polyclonal immunoglobulin-based product that could be purified from the eggs of vaccinated ducks (Anas platyrhynchos). The natural “despeciation" of the duck IgY (i.e., Fc removed) results in an immunoglobulin predicted to be minimally reactogenic in humans. Administration of ≥5,000 neutralizing antibody units (NAU)/kg of FFP-protected hamsters from lethal disease when given up to 8 days after intranasal ANDV challenge. IgY/IgYΔFc antibodies purified from the eggs of DNA-vaccinated ducks effectively neutralized ANDV in vitro as measured by plaque reduction neutralization tests (PRNT). Administration of 12,000 NAU/kg of duck egg-derived IgY/IgYΔFc protected hamsters when administered up to 8 days after intranasal challenge and 5 days after intramuscular challenge. These experiments demonstrate that convalescent FFP shows promise as a postexposure HPS prophylactic. Moreover, these data demonstrate the feasibility of using DNA vaccine technology coupled with the duck/egg system to manufacture a product that could supplement or replace FFP. The DNA vaccine-duck/egg system can be scaled as needed and obviates the necessity of using limited blood products obtained from a small number of HPS survivors. This is the first report demonstrating the in vivo efficacy of any antiviral product produced using DNA vaccine-duck/egg system.